PENGARUH STRES KERJA PADA CYBERLOAFINGÂ Â - HERLIANTO, ANINDITA WICAKSONO (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
The internet has become a necessity for many people as with the internet network can make people to search and find all sorts of information quickly and easily. So in the development of internet can provide positive impact. With the internet benefits. Employees are expected to to support in resolving tugas-tugasn they have. So the employees can follow the development of modern technology. But in practice there are only employees who hussy not to use the internet for his work called cyberloafing. In the sample population of this study was defined population is an employee who works in an office and use the computer facilities and is connected to the internet in work activities. The number of samples is examined as many as 100 samples. Sampling technique using probability sampling. Sampling in this study by way of distributing questionnaires. Analysis techniques using multiple regression analysis. Based on the results of calculations obtained that there is Role Ambiguity, Role Overload has a negative effect on Cyberloafing. Role Conflict has a positive influence on Cyberloafing.